Intestinal colonization with Candida auris and mucosal immune response in mice treated with cefoperazone oral antibiotic - Das, Diprasom; HogenEsch, Harm; Thangamani, Shankar (Frontiers in Immunology, 2023)
Candida auris, an emerging multi-drug resistant fungal pathogen, causes invasive infections in humans. The factors regulating the colonization of C. auris in host niches are not well understood. In this study, we examined the effect of antibiotic-induced gut dysbiosis on C. auris intestinal colonization, dissemination, microbiome composition and the mucosal immune response. Our results indicate that mice treated with cefoperazone alone had a significant increase in C. auris intestinal colonization compared to untreated control groups. A significant increase in the dissemination of C. auris from the intestine to internal organs was observed in antibiotic-treated immunosuppressed mice. Intestinal colonization of C. auris alters the microbiome composition of antibiotic-treated mice. Relative abundance of firmicutes members mainly Clostridiales and Paenibacillus were considerably increased in the cefoperazone-treated mice infected with C. auris compared to cefoperazone-treated uninfected mice. Next, we examined the mucosal immune response of C. auris infected mice and compared the results with Candida albicans infection. The number of CD11b+ CX3CR1+ macrophages was significantly decreased in the intestine of C. auris infected mice when compared to C. albicans infection. On the other hand, both C. auris and C. albicans infected mice had a comparable increase of the number of Th17 and Th22 cells in the intestine. Significant increase in the Candida-specific IgA was observed in the serum of C. auris but not in the C. albicans infected mice. Taken together, treatment with broad-spectrum antibiotic increased the colonization and dissemination of C. auris from the intestine. Furthermore, findings from this study for the first time revealed the microbiome composition, innate and adaptive cellular immune response to intestinal infection with C. auris.